Missed Opportunities and Hasty Decisions: Critical Analysis of Criminal Law Amendment Act, 2018 - Sharma, Abhishek (Trinity Law Review, 2021)
The two barbaric rape cases in Kathua and Unnao shook the conscience of the entire  nation. There was a huge public demand for stringent rape laws, which ultimately led  to the birth of Criminal law Amendment Act, 2018. Keeping in mind the accelerating  rate of sexual offences against women and to ensure women safety, the amendment was the need of the hour, still the amendment missed certain opportunities which were much  needed in India and it is high time to acknowledge some changes which are much  needed in Indian Criminal Law system dealing with sexual offences in India. This study  would focus upon some missed opportunities and some hasty and ill-conceived  decisions of the Legislature while dealing with the sexual offences in India in the said  amendment. Some of the missed opportunities and hasty and ill-conceived decisions in Criminal Law  Amendment Act, 2018: Whether introduction of death penalty in rape cases involving  child below 12 years of age is deterrent or is just a myth? Is increasing the punishment  from 10 to 20 years, when victim is of age between 12-16 years is justified even if the  sexual intercourse is consensual? Punishment under 376(1) is increased from 7 years  minimum to 10 years minimum making no difference with cases involving aggravated  rape. Is it justified to not give anticipatory bail to a person accused of an offence of  rape when victim is below 16 years of age?
Keywords: Criminal law Amendment Act; women safety; sexual intercourse